Effect of Geisel Agar culture medium from Moringa oleifera(Moringa) a viable approach on the growth of Escherichia coli - Villanueva Pedraza, Edwaldo (2022)
The objective of this study was to evaluate the effectiveness of the Geisel agar medium prepared at different concentrations of Moringa oleifera (Moringaceae) in comparison with a commercial medium on the growth and development of Escherichia coli strains. Microbial growth was evaluated at different concentrations of Moringa oleifera (Moringa), 0.1, 1 and 5% (w/v) in a culture medium called Geisel Agar and as a control a commercial agar plate culture medium. Bacteria were inoculated using a multiple streaking technique (with depletion) and then incubated to prevent condensation during incubation at 37 °C for 24 to 48 h. To evaluate the growth of strains expressed in colony-forming units, we considered cultural and microscopic characteristics. We conclude that an alternative culture medium prepared with a 1% dilution of Moringa oleifera Geisel agar contains the necessary and sufficient nutrients for the growth, development, survival and viability of the bacterium (Eschericha coli ATCC No. 8739).